Intralobar pulmonary sequestration complicated by gastric duplication - Shunsuke Watanabe; Tatuya Suzuki; Fujio Hara; Toshihiro Yasui; Naoko Uga; Atuki Naoe (Elsevier, 2017)
We experienced the case of an eight-month-old male with intralobar pulmonary sequestration complicated by gastric duplication. The chief complaint was an abnormal shadow on the chest radiograph; the patient was diagnosed with pulmonary sequestration via chest computed tomography (CT). Intraoperative findings and postoperative histopathological examination revealed intralobar pulmonary sequestration with associated gastric duplication. Pulmonary sequestration is relatively rare; although there are reports of extralobar pulmonary sequestration with gastric duplication, the present case of intralobar pulmonary sequestration with gastric duplication is extremely rare. This case is considered to be an embryologic bronchopulmonary foregut malformation, and is considered important in understanding the aetiology.